The Importance of Social Insurance in Human Capital Development - Asamxodjayeva Shoira Shukurullayevna (Genius Publishing Group, 2023)
The article examines the essence of social insurance relations in the formation and development of human capital. Areas of employer enterprises that affect human capital have been studied. Specific features of social insurance types have been considered.
Keywords: human capital; social insurance; education; medical assistance